Synthesis and characterization of sulfur functionalized mesoporous silicas as mercury adsorbents [electronic resource] - Norasikin Saman, 1985- (2011)
Thesis (Sarjana Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2011